Accessibility Assessment for Online Education Tools: Towards Accessible Principles for a Mexican University - S. Fajardo-Flores; L. Gaytan-Lugo; P. Santana-Mancilla; M. Rodriguez-Ortiz (European Alliance for Innovation (EAI), 2021)
INTRODUCTION: Characteristics of different disabilities using digital technologies are presented. Web content Accessibility Guidelines (WCAG) are explained according to their principles and how each offers alternatives for the limitations of people with disabilities and the conformance levels A, AA, AAA. OBJECTIVES: Perform an automatic evaluation of two digital educational platforms for students to validate the conformance with WCAG in the three levels.METHODS: Techniques derived from automatic checker assessment were used to complete this research.RESULTS: Results showed that to fix the accessibility issues level A, the technical difficulty is low. Likewise, the investment of time and money is not as significant compared to the benefits that it represents. CONCLUSION: Adopting the use of these automatic evaluation tools, developers will incorporate good accessibility practices as part of their experience.